PENGGUNAAN OBJECT-BASED LEARNING (OBL) MUSEUM SEJARAH BANGSA DAN TEMPAT-TEMPAT WISATA RELIGIUS UNTUK MEMBANGUN KESADARAN MULTIKULTURAL - Purwono Nugroho Adhi (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2022)
Building awareness of multiculturalism in Indonesia has indeed become a continuous and never-ending agenda. Indonesia as a country that has various ethnic groups, languages ​​and religions, of course, makes this awareness of multiculturalism important and important strategic. In almost a decade, there have been many communities, groups and institutions actively involved in efforts to build awareness of this multiculturalism. These efforts are intensified through various methods and approaches, both formally, informally and non-formally. There are many handbooks, references and guides that attempt in ways from academic to practical to try to implement this multiculturalism awareness education. One of the interesting things to strive for is the use of the Object-Based Learning method (OBL) museum of the nation's history and various religious tourist attractions. Why is the use of the Object-Based Learning (OBL) method in museums and various religious tourist attractions interesting to study as an effort to build awareness of multiculturalism. Object-Based Learning (OBL) or in simple terms as learning-based learning object, is a method or method that is often developed when visiting a museum. Rosalind Duhs associates Object-Based Learning (OBL) with the technique of utilizing exhibition objects in museums with various general or special collections for the learning process. In essence, through the museum's exhibition collection, students are invited to actively view artifacts museum. It is an attempt to link the pedagogical power of every museum collection (the pedagogical power of museum collections). In Michael's perspective Grimmitt, Object-Based Learning (OBL) can be a fabric of inter subjective understanding (inter-subjective) subjective understanding), so that it becomes a kind of educational constructivism power. That is, a person will gain a new understanding of what he has seen and learned by learning through Object-Based Learning (OBL) from religious tourist attractions, both the objects that exist, and the atmosphere they build. This paper describes how Object-Based Learning (OBL) National History Museums and Religious Tourist Places can be used to build multicultural awareness. The intended explanation is more of a methodological offer with theoretical and practical notes as well as examples that have been developed